2012
DOI: 10.1590/s0066-782x2012005000091
|View full text |Cite
|
Sign up to set email alerts
|

Ponto ótimo cardiorrespiratório: uma variável submáxima do teste cardiopulmonar de exercício

Abstract: Background: At the maximal Cardiopulmonary Exercise Testing (CPET), several ventilatory variables are analyzed, including the ventilatory equivalent for oxygen (VE/VO2). The minimum VE/VO2 value reflects the best integration between the respiratory and cardiovascular systems and may be called "Cardiorespiratory Optimal Point (COP)".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…In the present study, approximately 20% of patients were unwilling to complete a truly maximal CPX, making submaximal cardiorespiratory data even more relevant. As previously stated, premature CPX interruption tends to do not affect COP determination, since COP occured at about 44% of VO 2 max and so, well before anaerobic threshold and maximal effort [18]. This is further corroborated by the fact that PDG and CG did not have different COP results, and there was no difference in COP when comparing between subgroups of PD patients (Figure 1).…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…In the present study, approximately 20% of patients were unwilling to complete a truly maximal CPX, making submaximal cardiorespiratory data even more relevant. As previously stated, premature CPX interruption tends to do not affect COP determination, since COP occured at about 44% of VO 2 max and so, well before anaerobic threshold and maximal effort [18]. This is further corroborated by the fact that PDG and CG did not have different COP results, and there was no difference in COP when comparing between subgroups of PD patients (Figure 1).…”
Section: Discussionsupporting
confidence: 76%
“…When investigating COP behavior of PD patients (Figure 2) by using a regression equation [18], our results show that COP was about always (except in a single case), within the boundaries of estimate of error for healthy subjects. Therefore, it was observed that, from the point of view of cardiorespiratory integration, reflecting, at least partially, the quality of ventilation-perfusion ratio during exercise, PD patients exhibit no limitations and behave similarly to healthy subjects.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations